Performance Practice in a Pandemic: Training Ensemble Skills Using E-Tivities in Music Teacher Education - Karkina, Svetlana; Faizrakhmanova, Lyalya; Kamalova, Ilmira; Akbarova, Gulnaz; Kaur, Balwinder (Frontiers in Education, 2022)
The emergency situation due to the spread of COVID-19 has brought new requirements to Higher Education to continue the learning process. In musical ensemble class, performance practice is mandatory and plays a crucial role in musical education. The pandemic has forced all classes online, but for performance practice, it was mandatory to implement a new type of student-teacher interaction, such as e-tivity. It is a dynamic and interactive learning process led by a teacher online. The investigation of the efficiency of e-tivity for training musical ensemble skills was carried out in this paper. The research was tested through experimental work that took place at Kazan Federal University (Russian Federation). Due to a complete shift in the education process to distanced learning, all disciplines were studied online, including the specific musical courses that required collective work with face-to-face interaction. The curriculum of future music teachers includes an ensemble basic course to train students‘ musical performance skills in groups. For the study, 114 students from classes with instrumental and vocal ensembles were gathered and were organized by means of e-tivity based on several online tools, including Aiseesoft Video Converter Ultimate. This tool creates a video with a split-screen effect. By using such a tool, students created the video by following the teacher‘s instructions separately, and afterward they united their musical records in one video with a split-screen effect. At the end of the research work, musical artworks belonging to certain art styles, namely classical, Tatar and Russian folk music, and jazz, were collected. The analysis of the obtained data exhibited a high level of results in each criterion scale and effectiveness of the online work with musical ensembles. Students saw improvement in self-education by the means of creativity and critical self-assessment. The increasing frequency of students‘ listening of their own performance during the ensemble music-making by e-tivity brought advantages for the involuntary repetition process.